Quantitative targeted absolute proteomics of human blood–brain barrier transporters and receptors - Uchida, Yasuo; Ohtsuki, Sumio; Katsukura, Yuki; Ikeda, Chiemi; Suzuki, Takashi; Kamiie, Junichi; Terasaki, Tetsuya (Journal of neurochemistry, 2011)
J. Neurochem. (2011) 117, 333–345. We have obtained, for the first time, a quantitative protein expression profile of membrane transporters and receptors in human brain microvessels, that is, the blood–brain barrier (BBB). Brain microvessels were isolated from brain cortexes of seven males (16–77 years old) and protein expression of 114 membrane proteins was determined by means of a liquid chromatography–tandem mass spectrometric quantification method using recently established in‐silico peptide selection criteria. Among drug transporters, breast cancer resistance protein showed the most abundant protein expression (8.14 fmol/μg protein), and its expression level was 1.85‐fold greater in humans than in mice. By contrast, the expression level of P‐glycoprotein in humans (6.06 fmol/μg protein) was 2.33‐fold smaller than that of mdr1a in mice. The organic anion transporters reported in rodent BBB, that is, multidrug resistance‐associated protein, organic anion transporter and organic anion‐transporting polypeptide family members, were under limit of quantification in humans, except multidrug resistance‐associated protein 4 (0.195 fmol/μg protein). Among detected transporters and receptors for endogenous substances, the glucose transporter 1 level was similar to that of mouse, while the L‐type amino acid transporter 1 level was fivefold smaller than that of mouse. These findings should be useful for understanding human BBB function and its differences from that in mouse.